FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI SUAMI DALAM MENGIKUTI VASEKTOMI DI DESA PALUH SIBAJI KECAMATAN PANTAI LABU TAHUN 2018 - Lia Rosa Veronika Sinaga; Ernawati Barus; Anggi Devi Hapsari (Jurnal Mutiara Kesehatan Masyarakat, 2018)
Since the Indonesian population increases, one of the government’s efforts is to hold down its growth by vasectomy procedure. Some factors which influence vasectomy are wife’s support, wife’s knowledge, and family’s economic status. The objective of the research was to find out husband’s participation in having vasectomy at Paluh Sibaji Village, Pantai Labu Sub-district, in 2018. Vasectomy is the cutting off vas deferens, the duct which flow sperm from epididymis in testis seminalis.By the cutting off vas deferens, sperm cannot be ejaculated and the man becomes unproductive since vas deferens is clear from sperm. The research used case-control design which was aimed to find out the correlation of the factor of couple and the economic factor with husband’s participation in vasectomy at Paluh Sibaji Village, in 2018. The case group consisted of 38 wives whose husbands participated in vasectomy, and the control group consisted of 76 wives whose husbands did not participate in vasectomy (2:1). The result of chi square test showed that there was the correlation among the three factors. Husbands’ participation in vasectomy had significant correlation with wives’ support. They had the closest relation to their husbands, had good knowledge, and had confidence that their husbands would be all right. There was the correlation between family’s economic status and husbands’participation in vasectomy. Family’s bad economic status would choose vasectomy as the contraceptive device since it was done for good. It is recommended that counseling be provided so that information canbe accepted by all people.